The Relationship Between COVID-19 Severity and Some Diagnostic Methods - Alaa A. Saleh; Entiha Abdul-Zahra Abdul-Kareem; Abeer Al Sawafi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Coronavirus Disease 2019 (COVID-19), caused by SARS-CoV-2, presents heterogeneous clinical manifestations ranging from asymptomatic to severe conditions, necessitating reliable laboratory indicators for clinical stratification. Specific Background: Several diagnostic approaches, including RT-PCR and serological testing, are used to confirm infection; however, additional biomarkers such as IgM, IgG, C-reactive protein (CRP), ferritin, erythrocyte sedimentation rate (ESR), and platelet count have been reported in hospitalized patients. Knowledge Gap: Limited data are available regarding the gradient patterns of serological and inflammatory biomarkers across non-severe and severe COVID-19 groups within a single hospitalized cohort. Aims: This study measured IgM, IgG, CRP, ferritin, ESR, and platelet levels and examined their association with disease severity among 58 RT-PCR–confirmed patients. Results: Non-severe cases constituted 86.21% of patients, while 13.79% were severe. IgM seropositivity was higher than IgG in both groups, reaching 100% in severe cases. IgG positivity increased after the first week of infection and was detected in 83.33% of severe patients. CRP levels were elevated in all non-severe cases, whereas ferritin and ESR were particularly increased in moderate cases. Platelet count, CRP, ferritin, and ESR were significantly higher in the severe group (p<0.05). Age showed a positive correlation with severity (r=0.379). Novelty: The study demonstrates a distinct biomarker gradient linking antibody dynamics and inflammatory indices with clinical severity in a defined hospitalized population. Implications: Combined assessment of IgM, IgG, CRP, ferritin, and ESR may support early risk stratification and clinical decision-making in COVID-19 management. Highlights: • Severe Cases Exhibited Markedly Elevated Crp, Ferritin, Esr, and Platelet Values Compared With Non-Severe Cases.• Igm Seropositivity Exceeded Igg Across Clinical Categories, Reaching Complete Detection in Critical Patients.• Increasing Age Showed a Positive Correlation With Worsening Clinical Classification. Keywords: COVID-19 Severity, Serological Biomarkers, Inflammatory Markers, C-Reactive Protein, Erythrocyte Sedimentation Rate